2016
DOI: 10.1103/physrevd.94.065040
|View full text |Cite
|
Sign up to set email alerts
|

Fate of nonpolynomial interactions in scalar field theory

Abstract: We present an exact RG (renormalization group) analysis of O(N )-invariant scalar field theory about the Gaussian fixed point. We prove a series of statements that taken together show that the non-polynomial eigen-perturbations found in the LPA (local potential approximation) at the linearised level, do not lead to new interactions, i.e. enlarge the universality class, neither in the LPA or treated exactly. Non-perturbatively, their RG flow does not emanate from the fixed point. For the equivalent Wilsonian ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 84 publications
(233 reference statements)
0
28
0
Order By: Relevance
“…This was analysed in great detail in ref. [12], see also [10,11], however the focus there was different and model approximations were used (in particular the so-called Local Potential Approximation). Here, and in the rest of this paper, we make no approximations beyond the use of perturbation theory where it is legitimate to do so.…”
Section: Scalar Field Theory With Positive Kinetic Termmentioning
confidence: 99%
See 2 more Smart Citations
“…This was analysed in great detail in ref. [12], see also [10,11], however the focus there was different and model approximations were used (in particular the so-called Local Potential Approximation). Here, and in the rest of this paper, we make no approximations beyond the use of perturbation theory where it is legitimate to do so.…”
Section: Scalar Field Theory With Positive Kinetic Termmentioning
confidence: 99%
“…Their large field behaviour grows as ∼φ λ−5 exp(a 2φ2 ), so they lie outside L + . However it is not true that these solutions provide new continuum limits [10][11][12]. The reason is that for fixed , no matter how small, the linearised approximation, (2.5) or (2.22), is not valid for large field.…”
Section: From (23) the Eigenoperator Equation Is Thusmentioning
confidence: 99%
See 1 more Smart Citation
“…for perturbations around nontrivial solutions. In fact, the importance of a proper choice of the Hilbert space for spanning the fixed functions is also well studied for the analysis of fixed potentials in field space for Wilson-Fisher type fixed points 99,123,124 and beyond [125][126][127][128][129] . We observe a similar feature here for fixed functions in momentum space in the form of the maximum regularity criterion.…”
Section: A Pointlike Limitmentioning
confidence: 99%
“…In d = 4 the situation is complicated and a debate over the significance of the nonpolynomial solutions of (10) has continued for a long time (see e.g. a recent work 17 and references therein). To incorporate this scalar field theory into an inflation model, Huang et al suggested in ref.…”
Section: Halpern-huang Potential and Inflationmentioning
confidence: 99%